2021
DOI: 10.1108/aea-05-2020-0051
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of demand and exchange rate shocks in the tourism sector

Abstract: Purpose This study aims to measure the relationship between demand and exchange rate shocks in the tourism industry. Design/methodology/approach A panel data set is constructed covering the period between 1995 and 2017, and the data set includes the top 26 countries that host 10 million tourists and above in the world as of 2017. The standard errors of the series are used as an indicator of shocks. First, the cross-sectional dependency, stationarity and the homogeneity of the series are examined; second, a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…Similarly, the exchange rate significantly increases tourism receipts at the 5% significance level. This result also conforms to previous findings (Ergen & Yavuz, 2017;Meo et al, 2018);Chi, 2020;Athari et al, 2020;Boskurt et al, 2021). This intuitively implies that the increase in of Sri Lankan Rupee to the US dollar (depreciation) will increase the demand for tourism, increasing the tourism receipt.…”
Section: Unit Root Test and Cointegration Resultssupporting
confidence: 92%
“…Similarly, the exchange rate significantly increases tourism receipts at the 5% significance level. This result also conforms to previous findings (Ergen & Yavuz, 2017;Meo et al, 2018);Chi, 2020;Athari et al, 2020;Boskurt et al, 2021). This intuitively implies that the increase in of Sri Lankan Rupee to the US dollar (depreciation) will increase the demand for tourism, increasing the tourism receipt.…”
Section: Unit Root Test and Cointegration Resultssupporting
confidence: 92%
“…Vanegas and Croes also found the exchange rate to be an insignificant determinant of tourism demand to Aruba from the United States. These findings were supported by other studies such as Baran et al (2019), Bozkurt et al (2021) Catalbas (2016), Cheng et al (2013, Dhaoui et al (2017), Dogru et al (2017), Glauco andKhine (2013) and Samirkas and Samirkas (2015).…”
Section: Empirical Reviewsupporting
confidence: 87%
“…Exchange rate has PLOS ONE asymmetric impact on tourism on tourism development in developing countries such as, India, Bangladesh, Pakistan and Nepal in the short run [41]. Boskurt et al [42] applied dynamic common correlated effects (DCCE) approach in their study on demand and exchange rate shocks on tourism development and concluded that effects of the exchange rate shocks are temporary on the tourism development. To examine the response of tourism demand to exchange rate fluctuation in South Korea, Chi [43] used ARDL model and concluded that tourists are sensitive to the appreciation of the Korean Won, whereas they are insensitive to its depreciation.…”
Section: Tourism and Exchange Ratementioning
confidence: 99%
“…Existing literature have found a positive relationship between different dimensions of tourism and economic growth [61][62][63][64][65]. The second key explanatory variable is exchange rate [42,[66][67][68]. The exchange rate captures the competitiveness of a country in the international market [69][70][71][72][73].…”
Section: Main Explanatory Variablesmentioning
confidence: 99%